Pengaruh Brand Awareness, Live Streaming, Review, dan Rating terhadap Keputusan Pembelian Produk Binasyifa di Shopee - Zahra, Arista Viftania Az; Sadiyah, Fitria Naimatu; Rahayu, Novia Aristi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to determine the influence of brand awareness, live streaming, review, and rating on the purchase decision of Binasyifa Products on shopee, both simultaneously and partially. The method used in this research is quantitative with a non probability sampling technique, specifically purposive sampling. The study involved 68 samples consisting of consumers who purchased Binasyifa Products through shopee live streaming. Data analysis was conducted using multiple linear regression, assisted by SPSS version 25. The results show that simultaneously, brand awareness, live streaming, review, and rating have an influence on the purchase decision of Binasyifa Products on shopee. Partially, brand awareness and live streaming do not have a significant effect on the purchase decision of Binasyifa Products on shopee. However, review and rating partially have a significant influence on the purchase decision of Binasyifa Products on shopee.